Antibacterial Activity of Volatile Components From Citrus reticulata - Pachori, Kanti (Asian Journal of Chemistry, 2010)
The volatile components from Citrus reticulata leaves were tested and found to have adequate antibacterial activity against the tested organism in comparing to the standard drugs. Various essential oils have been reported to be associated with antibacterial activity. Therefore present investigations were carried out with a view to examine the antibacterial acitvity of the oil from the leaves of Citrus reticulata.